Relationship between Timed Up and Go performance and quantitative biomechanical measures of balance - Tendolkar, Prasad; Ibironke, Oluwaseun; Marchesi, Giorgia; De Luca, Alice; Squeri, Valentina; Nolan, Karen J.; Pilkar, Rakesh; Karunakaran, Kiran K. (Frontiers in Rehabilitation Sciences, 2024)
Traumatic brain injury (TBI) impairs sensory–motor functions, with debilitating consequences on postural control and balance, which persist during the chronic stages of recovery. The Timed Up and Go (TUG) test is a reliable, safe, time-efficient, and one of the most widely used clinical measures to assess gait, balance, and fall risk in TBI patients and is extensively used in inpatient and outpatient settings. Although the TUG test has been used extensively due to its ease of performance and excellent reliability, limited research has been published that investigates the relationship between TUG performance and quantitative biomechanical measures of balance. The objective of this paper was to quantify the relationship between biomechanical variables of balance and the TUG scores in individuals with chronic TBI. Regression models were constructed using six biomechanical variables to predict TUG scores. The model that conservatively removed gait speed (i.e., TUG-1/GS) gave the best results, achieving a root-mean-square error of ∼±2 s and explaining over 69% of the variability.